The effect of environmentally friendly packaging on consumer preference within the cosmetics industry in KwaZulu-Natal - Daniel, Cooper (The IIE, 2020)
The effects of packaging waste from cosmetic products is a worldwide problem and has been described by many academics as a severe environmental threat. Environmental sustainability is growing in importance as consumers become increasingly aware of its necessity. This quantitative research study focuses on whether environmentally friendly packaged cosmetic products has an effect on consumer preference in KwaZulu-Natal. South Africa has an emerging cosmetic market which could benefit from the use of environmentally friendly packaging. Icek Ajzen’s Theory of Planned Behaviour (1991) has been used as a foundation to describe consumer behaviour. Data was collected using a closed-ended questionnaire as objectivity was important and the data obtained was easy to analyse and quantify. The research indicated that cost plays an important role in consumer spending in the cosmetic market. It was also found that cosmetic consumers are brand loyal and that the primary household shopper has control over products individuals in the household use. The results indicate that there is a link between consumer purchasing preference and cosmetic products that make use of environmentally friendly packaging. Therefore, cosmetic manufacturers in KwaZulu-Natal should incorporate environmentally friendly packaging into their products, potentially leading to an increase in sales and market share.
Keywords: Environmentally friendly packaging; Consumer preferences; Cosmetics industry